KEEKTIFAN MODEL TWO STAY TWO STRAY BERBASIS TEORI VAN HIELE DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS V SD NEGERI 018 KUBANG JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Ermawati Ermawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is based on mathematics learning at SD Negeri 018 Kubang Jaya which uses conventional learningmodel impact on the low of activity and result of learning which is indicated by the number of students who getvalue under Minimum Exhaustiveness criteria. The research design used was quasi experimental with nonequivalentcontrol group design. The population in this study are the students of class V SD Negeri 018 Kubang Jaya. Datacollection techniques used are unstructured interviews, observation, documentation, and tests. Based on the resultsof hypothesis test data of student learning activities with the calculation using independent sample t test, showedthat t count> t table (10,047> -2,011). Student learning result data indicate that t arithmetic> t table (3,221> -2,011) hence can be concluded activity and result of student learning at learning mathematics of wake up matterapplying model Two Stay Two Stray based Van Hiele theory higher than learning applying conventional model .Based on hypothesis test result using right side test formula, student activity data data show that t count>t table(16,664> -2,069) and significance value <0,05 (0,000 <0,05). Result of hypothesis test result of student learningshow that t count> t table (4,897> -2,069) and significance value <0,05 (0,000 <0,05). So the application of TwoStay Two Stray model based on van Hiele theory proved effective against activity and result of student learning onlearning mathematics of wake up matter.